Six Sigma as a quality improvement tool for academic programs - Cano, Emilio L.; González de Lena, M.; Moguerza, Javier; Redchuk, Andrés (My University, 2016)
In this work, we present a methodology for the design and improvement of academic programs based on Six Sigma. Six Sigma is a methodology for quality improvement [ISO 13053-1] well known in industrial environments that is being more and more used in services and administration areas. The proposed methodology is applied to the Internal Systems Quality Assurance (ISQA) in Information Technology and Communications (ITC) Schools, but it is easily generalizable to other schools and faculties. The Spanish National Agency for Quality Assessment and Accreditation (ANECA for its Spanish acronym) sets the guidelines for improving the ISQAs, but ANECA does not indicate how to implement them. Currently, there is a lack of methodologies to create and/or improve quality control systems for teaching and associated services. It is therefore necessary to explore other ways. As a first contribution, we are using successful quality improvement methodologies at the business level for academic purposes. Even though there are various methods for improving the quality of processes (EFQM, Kaizen, etc.), Six Sigma has proven to be among the best ones. Indeed, Six Sigma successfully adapted the scientific method in order to be straightforwardly applied to process improvement within organisations. Our second contribution, probably the most important one, is the development of a typology catalogue gathering the developed procedures structure. Such catalogue allows to systematically detect types of procedures and structures, representing by itself a novel tool. The remaining contributions are explicit descriptions of procedures for a particular ITC School. These descriptions showcase a comprehensive practical application of the proposed methodology. The integrated system developed in this work organises the procedures into three areas: strategic, operational and cross-cutting.
Keywords: six sigma; quality improvement; quality assurance; high education